Profile of neonatal dermatoses in a tertiary care teaching hospital of Haryana - Marwah, Poonam; Marwah, Ashish; Kumar, Sunil; Kumar, Rajesh (International Journal of Research in Medical Sciences, 2018)
Background: To assess the incidence and profile of neonatal dermatoses in a tertiary care hospital of Haryana and study its association with various perinatal risk factors. Methods: All inborn neonates (<28 days of life) including those seen in the outpatient department on follow up between November 2016 to April 2017 formed the baseline population and babies with skin lesions were included in the study. A detailed perinatal history and newborn examination of the baby was done by a pediatrician and all relevant details were recorded. Data was analyzed, and inferences were drawn using tables. Results: In our study, a total of 2760 newborn (1506 (54.6%) males and 1254 (45.4%) females) were studied. The incidence of neonatal dermatoses was found to be 94.1%. There were 1849 (66.9%) term, 853 (30.9%) preterm, and 58 (2.1%) post term neonates. 1901 (68.8%) had birth weight >2.5kg while 859 (31.1%) had birth weight ≤2.5kg. 1223 (44.3%) were born to primipara while 1537 (55.6%) were born to multipara mothers. Mothers of 54 (1.9%) neonates were < 20 years of age; 1157 (41.9%) in the age group of 20-25 years; 1324 (47.9%) in the age group of 25-30 years and 225 (8.1%) in the age group >30 years. 1806 (65.4%) neonates were born by normal vaginal delivery and 954 (34.6%) neonates were born by cesarean section. In 13 (0.5%) neonates, history of consanguinity was present while it was absent in 2747 (99.5%) neonates. Most common skin lesions observed were transient skin lesions among which Mongolian spots (62.9%), epstein pearls (48.8%), erythema toxicum (41.8%), milia (40.6%) and miniature puberty (35.9%) were the most common. Conclusions: Incidence of neonatal dermatoses was found to be higher (54.6%) among males as compared to females (45.4%); among term babies; those with birth weight >2.5kg; those born to multipara mothers; those born via normal vaginal delivery and those with maternal age 25-30 years.